Africa's experience with structural adjustment : proceedings of the Harare seminar, May 23-24, 1994 - Kapoor, Kapil; World Bank. (Washington, D.C. : World Bank, 1995)
This paper summarizes the proceedings of a seminar on structural adjustment in Africa, which was held in Harare, Zimbabwe, on May 23 - 24, 1994, and also includes papers presented by some of the participants.
Includes bibliographical references (p. 121-122).
osc 2/11/2021
Loans
Keywords: Structural adjustment (Economic policy)